2011
DOI: 10.1007/s00253-011-3793-2
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal activity of Musca domestica cecropin (Mdc) on multidrug-resistant clinical isolate of Escherichia coli

Abstract: The housefly (Musca domestica) larvae have been used clinically to cure osteomyelitis, decubital necrosis, lip boil, ecthyma and malnutritional stagnation ever since the Ming/Qing Dynasty (1368 Anno Domini) till now, in China. In prior research, we have cloned and characterized a new gene of antimicrobial peptide cecropin from M. domestica larvae. This peptide was potently active against Gram-positive and Gram-negative bacteria standard strain. In the present study, we evaluated the possibility of Mdc to be a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 19 publications
0
30
0
1
Order By: Relevance
“…D) [4]. During the past decade, due to the antibacterial activity of housefly larvae and its products, they have been used mainly in preservation [11], environmental protection [12], and inhibition of multiresistant bacteria [13]. In recent years, several reports suggested that atherosclerosis is a chronic inflammatory disease [14, 15] that can be accelerated by microbial infection in its early phase [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…D) [4]. During the past decade, due to the antibacterial activity of housefly larvae and its products, they have been used mainly in preservation [11], environmental protection [12], and inhibition of multiresistant bacteria [13]. In recent years, several reports suggested that atherosclerosis is a chronic inflammatory disease [14, 15] that can be accelerated by microbial infection in its early phase [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Kinetics of bacterial killing was determined according to the method described in Lu et al [22]. Log-phase A. baumannii strains GIM1.650 (10 6  CFU/mL) were incubated with culture medium containing zero or MIC, 1/4 MIC Mdc for 120 min.…”
Section: Methodsmentioning
confidence: 99%
“…A limitation for the transition of cecropin to therapeutic purpose is the hemolytic or cytotoxicity properties [21]. Of important note, Mdc did not show a perceptible cytotoxic effect on human red blood cells [22]. So, it is a subject for further studies whether Mdc will be a novel and effective clinical alternative against the increasing threat of a widespread dissemination of multidrug-resistant A. baumannii .…”
Section: Introductionmentioning
confidence: 99%
“…They are also popular in Latin American medicine for boils, baldness, eyesores, external sebaceus lamps, stye, ophthalmological problems, dermatosis, cysties and erysipelas 12 . In China, the use of housefly larvae to cure osteomyelitis, decubital necrosis, lip boil, ecthyma and malnutrition stagnation dates back to the Ming/Qing Dynasty 145 .…”
Section: Diptera (Flies and Mosquitoes)mentioning
confidence: 99%